Figurative Languages in William Shakespeare’s Poem: a Fairy Song, a Madrigal, Bridal Song, Dirge, and Sonnet 116 - Raflis Raflis; Juni Rahmat Zai (Fakultas Sastra Universitas Ekasakti, 2018)
The problem in this thesis is figurative language in Shakespeare's poetry. The reason for choosing the figurative language in William Shakespeare's poetry is because all of his works contain many literary qualities, which are figurative and each of these poems has a beautiful story that is translated into a beautiful figurative form.The purpose of this study is to analyze types of figurative language, figurative language formulas, and figurative language functions in Shakespeare's poetry. In this writing, library research is taken as a data collection method. As for the data analysis method, the researcher describes literary work as a not-based structure that forms it as an internal factor of literature. Data collection techniques use documentation techniques to find data relevant to the research. In data analysis techniques, the author uses a formalist approach, all elements needed to understand the work contained in the work itself. The main purpose for formalist criticism is to determine how elements in Shakespeare's poetry work together with text content to form meaning to the reader.The findings in this thesis are: 1) figurative language in Shakespeare's poetry can be divided into simile, metaphor, hyperbole, personification, and repetition. Simile can be found in Madrigal poetry; Metaphorical figurative languages ​​can be found in four Shakespearean poems, A Fairy Song, Song Bridal, Dirge, and Sonnet 116; personification can be found in two poems Shakespeare, A Madrigal and Dirge; hyperbole can be seen A Fairy Song, Dirge, and Sonnet 116; and Repetition can be seen in three poems of Shakespeare, A Fairy Song, A Madrigal, and Dirge.